University of the future: a conceptual model of university of the future - Sondria, Prilly Noverina; Maneechayangkoon, Nadia; Ahmad Dahlan, Abdul Rahman (Eclat Research Publication, 2016)
Stephens (2013) explains higher education is being challenged to meet inflated expectations and that creating the future requires collaboration across organizational and national boundaries. Moreover, Tight (2004) also explains that higher education research has grown substantially in importance over the last two decades. These statements emphasize higher education to change. In addition (Abeles, 2006,p.41 in Stephen, 2013) tells us that universities change continually. The purpose of this study is find out what is university of the future will be like. The methodology use the business model canvas (BMC) and value preposition design (VPD)canvas to analyze the results. The finding of the study shows that student would like to have quality knowledge with they apply it into real life.